L’horreur acoustique musiques « anempathiques » dans le théâtre de Martin Crimp - Aloysia Rousseau (Sillages Critiques)
The British playwright Martin Crimp suggests an ironic use of music and sounds in his stage directions. Antiphrasis is thus transposed from a textual semiotic system to an auditory semiotic system. Music is not illustrative but arouses on the contrary an “anempathetic” effect, an expression coined by Michel Chion in his book La Musique au cinéma. Martin Crimp exploits this anempathetic strategy in plays such as Play with Repeats (1990), The Treatment (1993) or more recently the triptych Fewer Emergencies (2005) in which violent events are narrated with a boogie-woogie playing in the background. The horror of the story is emphasized by the musical counterpoint. The joy which pervades the stage through the use of music is denounced as artificial.